42nd Jawaharlal Nehru National Science, Mathematics and Environment Exhibition (JNNSMEE) for Children - Gupta, Gagan (SCHOOL SCIENCE, 2015)
Organised by the Department of Education in Science and Mathematics. National Council of Educational Research and Training, Sri Aurobindo Marg, New Delhi 110016; in collaboration with the Government of Kerala. Venue: Nirmala College Campus, Muvattupuzha, Ernakulam, Kerala from 16 – 22 December 2015. The 42nd Jawaharlal Nehru National Science, Mathematics and Environment Exhibition (JNNSMEE) for Children – 2015 was inaugurated on 16 December, 2015 by Padma Bhushan Dr. K. Radhakrishnan, a renowned Indian space scientist and former Chairman of the Indian Space Research Organization (ISRO), and presently the Chairman of the Indian Institute of Engineering Science and Technology at the Nirmala College Campus, Muvattupuzha, Ernakulam, Kerala. The inaugural function was also graced by Sri Joseph Vazhakkan, MLA; Professor Hrushikesh Senapaty, Director, NCERT; Smt. Usha Sasidharan, Municipal Chairperson, Muvattupuzha, Mar George Madathikandathil, the Bishop of Kothamangalam Diocese; and other dignitaries of Kerala Government, NCERT and Nirmala College Campus.